346 RENOPROTECTIVE ACTIONS OF BONE MARROW-DERIVED MESENCHYMAL STEM CELLS ARE A POTENTIAL NEW TREATMENT FOR ACUTE RENAL FAILURE. (1st January 2006) - Toegel, F. E.; Hu, Z.; Weiss, K.; Isaac, J.; Clayton, F.; Westenfelder, C.
Abstract : Since acute renal failure (ARF) remains a common clinical syndrome with high mortality rates and limited treatment options, fundamentally new interventions are needed. We reported recently (Am J Physiol and Kidney Int 2005) that the infusion of mesenchymal stem cells (MSCs) is strikingly renoprotective in rats with severe ischemic ARF. Because essentially no transdifferentiation of small numbers of MSCs in the kidney was detected, we investigated alternative renoprotective mechanisms. We found striking down-regulation of proinflammatory TNF-α, IL-1β, and IFN-γ, and up-regulation of anti-inflammatory IL-10 and antiapoptotic Bcl-2, while leukocyte infiltration was similar. MSC treatment induced tubular up-regulation of bFGF and TGF-α. Renal artery and cortical blood flows were not different in MSC vs control animals. We next tested the effect of MSC conditioned medium (MSC-CM) on endothelial cells (ECs). MSC-CM acted mitogenically and inhibited apoptosis, a response also observed in tubular cells. Because growth factor (GF) expression by MSCs (express VEGF, HGF, and IGF-I, all act renoprotectively in ARF) is another potential mediator of renoprotection and since pO2 in the ischemic kidney is low, we found that VEGF expression in MSCs cultured at 5% pO2 was markedly upregulated. Our data show that the renoprotective actions of MSCs in ARF are mediated primarily through paracrine mechanisms. These elicit powerful anti-inflammatory, antiapoptotic, and mitogenic responses in renal cells that together result from the intrarenal delivery of GFs by MSCs and from their induction in the kidney of additional protective growth factors. In conclusion, we posit that our data provide the basis for the development of an MSC-based therapy for clinical ARF.